Prophylactic immunization with human papillomavirus vaccines induces oral immunity in mice. (4th September 2017) - Ahn, Julie; Peng, Shiwen; Hung, Chien‐Fu; Roden, Richard B. S.; Best, Simon R.
Abstract : Objective: Although it has been shown that prophylactic vaccination can induce genital immunity, there is inadequate information on human papillomavirus (HPV) vaccine‐induced oral immunity, which is of particular interest due to HPV‐associated oropharyngeal malignancies and recurrent respiratory papillomatosis. Therefore, we assessed the efficacy of various HPV vaccines against oral HPV pseudovirus (PsV) infection in mice. Study Design: Preclinical scientific investigation. Methods: C57BL/6 mice were vaccinated three times at 2‐week intervals with either Gardasil (Merck, Kenilworth, NJ) (50 µL intramuscular injection) or a candidate pan‐HPV L2 vaccine with alum adjuvant (25 µg subcutaneous injection). Additional mice were immunized with passive transfer of either Gardasil (Merck) human antisera or nonimmunized sera (100 µL intraperitoneal injection). All vaccinated and naïve control mice were then challenged with HPV16 E6E7 luciferase PsV in the oral mucosa. Visualization of HPV PsV infection was monitored through in vivo luciferase imaging. Results: Oral luciferase‐expressing HPV16 PsV infection was not detected in Gardasil (Merck), L2 vaccine, and Gardasil (Merck) antisera‐immunized mice, whereas robust luciferase expression was observed in all control mice. An in vitro neutralization assay from sera of Gardasil‐vaccinated (Merck) mice confirmed that vaccine efficacy was due to neutralizing antibodies. Conclusion: Oral HPV16 PsV infection in mice was completely prevented with all methods of prophylactic HPV immunization. These findings provide preliminary evidence that human vaccines induce protection against oral HPV infection, which has significant public health implications for HPV‐associated oropharyngeal malignancies. Level of Evidence: NA. Laryngoscope, 128:E16–E20, 2018